2014
DOI: 10.1021/ar500083f
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Control of Channel Interference in Two-Photon Absorption Processes

Abstract: The two-photon absorption (TPA) process is the simplest and hence the most studied nonlinear optical phenomenon, and various aspects of this process have been explored in the past few decades, experimentally as well as theoretically. Previous investigations have shown that the two-photon (TP) activity of a molecular system can be tuned, and at present, performance-tailored TP active materials are easy to develop by monitoring factors such as length of conjugation, dimensionality of charge-transfer network, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 61 publications
0
53
0
Order By: Relevance
“…This analysis was first proposed by Ågren and co-workers 19 for two-dimensional systems wherein only two components of the transition moment vectors are involved. Alam et al [20][21][22] proposed a general model that can be used for any molecule, irrespectively of its dimensionality.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis was first proposed by Ågren and co-workers 19 for two-dimensional systems wherein only two components of the transition moment vectors are involved. Alam et al [20][21][22] proposed a general model that can be used for any molecule, irrespectively of its dimensionality.…”
Section: Introductionmentioning
confidence: 99%
“…All materials and solvents are commercially available.Infrared spectra were obtained on a FTIR Varian Spectrometer ATR. Melting points were obtained in an Electrothermal-9200 1. H and 13 C NMR spectra, were taken in a JEOL eclipse ECA +500 spectrometer, the chemical shifts in ppm are relative to (CH 3 )4 Si for1 H and 13 C. High resolution TOF-MS mass spectra were recorded on an Agilent G1969A spectrometer.…”
mentioning
confidence: 99%
“…Chattopadhyaya et al [18] have shown that the number of D/A groups cannot be the sole criteria for larger TPA cross-section; rather, the D/A groups at a suitable position can lead to a large dipole moment difference between the ground and excited state, which is ultimately responsible for the high TP activity of bisanthene and D/A substituted bisanthene molecule. Apart from all these factors, Cronstrand et al [19,20] and Alam et al [21,22] have shown that as the excitation from ground to excited state takes place through several optical pathways by the involvement of several intermediate states, the interference between different optical channels also have a crucial role in determining the overall TP activity of a molecule. Cronstrand et al have scrutinized the role of interference between different optical channels and derived a two-dimensional four-state model formula to demonstrate the role of some selective chromophores on TP activity.…”
Section: Introductionmentioning
confidence: 99%